Comparing Plasma Donor-derived Cell-free DNA to Gene Expression in Endomyocardial Biopsies in the Trifecta-Heart Study - Halloran, Philip F; Reeve, Jeff; Mackova, Martina; Madill-Thomsen, Katelynn S; Demko, Zachary; Olymbios, Michael; Campbell, Patrick; Melenovsky, Vojtech; Gong, Timothy; Hall, Shelley; Stehlik, Josef (Transplantation, 2024)
BACKGROUND: Plasma donor-derived cell-free DNA (dd-cfDNA) is used to screen for rejection in heart transplants. We launched the Trifecta-Heart study ( ClinicalTrials.gov No. NCT04707872), an investigator-initiated, prospective trial, to examine the correlations between genome-wide molecular changes in endomyocardial biopsies (EMBs) and plasma dd-cfDNA. The present report analyzes the correlation of plasma dd-cfDNA with gene expression in EMBs from 4 vanguard centers and compared these correlations with those in 604 kidney transplant biopsies in the Trifecta-Kidney study ( ClinicalTrials.gov No. NCT04239703). METHODS: We analyzed 137 consecutive dd-cfDNA-EMB pairs from 70 patients. Plasma %dd-cfDNA was measured by the Prospera test (Natera Inc), and gene expression in EMBs was assessed by Molecular Microscope Diagnostic System using machine-learning algorithms to interpret rejection and injury states. RESULTS: Top transcripts correlating with dd-cfDNA were related to genes increased in rejection such as interferon gamma-inducible genes (eg, HLA-DMA ) but also with genes induced by injury and expressed in macrophages (eg, SERPINA1 and HMOX1 ). In gene enrichment analysis, the top dd-cfDNA-correlated genes reflected inflammation and rejection pathways. Dd-cfDNA correlations with rejection genes in EMB were similar to those seen in kidney transplant biopsies, with somewhat stronger correlations for TCMR genes in hearts and ABMR genes in kidneys. However, the correlations with parenchymal injury-induced genes and macrophage genes were much stronger in hearts. CONCLUSIONS: In this first analysis of Trifecta-Heart study, dd-cfDNA correlates significantly with molecular rejection but also with injury and macrophage infiltration, reflecting the proinflammatory properties of injured cardiomyocytes. The relationship supports the utility of dd-cfDNA in clinical management of heart transplant recipients.
Keywords: dospělí; Biopsy; Prospective Studies; Kidney Transplantation; Predictive Value of Tests; Humans; lidé středního věku; myokard; biopsie; dárci tkání; prospektivní studie; Middle Aged; Tissue Donors; Cell-Free Nucleic Acids; transplantace ledvin; transplantace srdce; mužské pohlaví; Adult; biologické markery; volné cirkulující nukleové kyseliny; ženské pohlaví; rejekce štěpu; stanovení celkové genové exprese; lidé; Gene Expression Profiling; Graft Rejection; Biomarkers; Myocardium; Aged; prediktivní hodnota testů; senioři; Male; Heart Transplantation; Female